Efficacy of Uterovaginal Packing Versus Uterine Balloon Tamponade to Control Postpartum Hemorrhage Due to Uterine Atony - Nasreen Kishwar; Rubina Akhter; Shazia Tabassum; Rukhsana Karim; Rabeea Sadaf; Samreen (Gandhara University, 2023)
OBJECTIVES To determine and compare the efficacy of Uterovaginal packing versus uterine balloon tamponade to control postpartum haemorrhage due to uterine atony unresponsive to medical treatment. METHODOLOGY This comparative prospective cross-sectional study was conducted in Hayatabad Medical Complex, OBG department. A total of 140 patients were categorised into two groups, group A underwent Uterovaginal packing and group B underwent uterine balloon tamponade. All women of 18 to 40 years with a history of delivery after 28 weeks of gestation, who developed primary postpartum haemorrhage due to uterine atony, unresponsive to medical treatment were included in the study. Women with a history of delivery before 28 weeks of gestation, secondary postpartum haemorrhage, genital tract trauma, retained placental tissue and membranes, placenta previa, morbidly adherent placenta, febrile illness and uterine structural lesion were excluded from the study. Efficacy was labelled if there was no ongoing blood loss after the procedure with concomitant hemodynamic stability. All information was recorded in a predesigned proforma, and data were analysed using SPSS version 22. RESULTS Our study included 140 women; 113 had a normal vaginal delivery, and 27 underwent cesarean section. Among cases with normal vaginal delivery, 45 women had Uterovaginal packing, and 68 had uterine balloon tamponade, while among cases of cesarean sections, 25 women had uterovaginal packing and 2 had uterine balloon tamponade. The efficacy of Uterovaginal packing was 90%, and that of uterine balloon tamponade was 87.1%, with no significant difference statistically (p- 0.51). Overall efficacy of both procedures was 88.6%. CONCLUSION All orthodontic and non-orthodontic treatment group participants required oral hygiene instructions and had periodontal treatment needs (TN1). The patients requiring scaling and prophylaxis and Oral hygiene instructions (TN 2) were more in the orthodontic treatment group than the non-orthodontic treatment group. A higher percentage of patients requiring complex treatment (deep scaling, root planning and complex surgical procedures), scaling and prophylaxis and Oral hygiene instructions (TN3) belonged to the non-orthodontic treatment group.